2004
DOI: 10.1159/000078175
|View full text |Cite
|
Sign up to set email alerts
|

Lung and Brain Damage in Preterm Newborns

Abstract: The relationships among bronchopulmonary dysplasia (BPD), brain white matter damage (WMD) and cerebral palsy (CP) are far from simple. Apparently, BPD and WMD are not associated, while BPD and CP are. The most likely explanation for this paradox is that ultrasound imaging does not identify all the WMD that might lead to CP (‘tip-of-the-iceberg effect’). We discuss further methodological inconsistencies, etiological peculiarities related to antenatal infection/inflammation, and intervention-related issues. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…Perinatal inflammation has been associated with a number of adverse neurological outcomes in preterm infants such as white matter injury, intraventricular hemorrhage, cystic periventricular leukomalacia and cerebral palsy [23,70,71,72]. Maternal intrauterine infection and inflammation can induce a production of proinflammatory cytokines in the fetal brain such as tumor necrosis factor-α (TNF-α) and interleukins (IL)-1, IL-6, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal inflammation has been associated with a number of adverse neurological outcomes in preterm infants such as white matter injury, intraventricular hemorrhage, cystic periventricular leukomalacia and cerebral palsy [23,70,71,72]. Maternal intrauterine infection and inflammation can induce a production of proinflammatory cytokines in the fetal brain such as tumor necrosis factor-α (TNF-α) and interleukins (IL)-1, IL-6, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that perinatal inflammation and infection may have a deleterious effect on the developing blood vessels in the retina, making them vulnerable to the development of ROP. In a number of recently published studies, histological CA has in fact been shown to be an important risk factor for the development of early-onset sepsis as well as subsequent neonatal disorders of the lung, intestines and brain including white matter injuries and intraventricular hemorrhage [17,18,19,20,21,22,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…6 Preeclampsia, as a pathophysiologic condition, is now known to be associated with fewer adverse neurologic outcomes in newborns than other obstetric complications, such as the fetal inflammatory response syndrome, so often seen in preterm premature rupture of the membranes. 8 In one recent study conducted outside the United States among preeclamptic mothers, virtually none of whom had received MgSO 4 prophylaxis, no child was later found to have cystic periventricular leukomalacia (cPVL), an important risk factor for subsequent CP. 9 Thus, despite the absence of magnesium exposure, there appears to be some, as yet to be characterized, biological factor in the pathogenesis of maternal preeclampsia that is inherently neuroprotective for babies.…”
Section: Initial Magnesium and Cp Hypothesismentioning
confidence: 99%
“…1 The term chorioamnionitis refers to both the clinical syndrome of intrauterine infection and the histological process responsible for it. Most important, chorioamnionitis is often clinically silent.…”
Section: Introductionmentioning
confidence: 99%